1999
DOI: 10.1007/s001250051282
|View full text |Cite
|
Sign up to set email alerts
|

A paired-sibling analysis of the XbaI polymorphism in the muscle glycogen synthase gene

Abstract: Impaired insulin-stimulated peripheral glucose uptake represents an early metabolic defect in the development of Type II ( non-insulin-dependent) diabetes mellitus [1,2] and results primarily from impaired non-oxidative glucose metabolism, i. e. glycogen synthesis in skeletal muscle [1,3]. The impairment in insulin-stimulated glycogen synthesis has been associated with impaired activation of glycogen synthase [4±6]. Deterioration in insulin-stimulated glycogen synthase activity has been consistently shown in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
20
0
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 40 publications
4
20
0
1
Order By: Relevance
“…Our results are particularly interesting in light of the recent report of Orho-Melander et al (6), which showed increased susceptibility of XbaI polymorphism carriers to hypertension, insulin resistance, and earlier onset of type 2 diabetes. Our data provide clues to a mechanism that may explain their results.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Our results are particularly interesting in light of the recent report of Orho-Melander et al (6), which showed increased susceptibility of XbaI polymorphism carriers to hypertension, insulin resistance, and earlier onset of type 2 diabetes. Our data provide clues to a mechanism that may explain their results.…”
supporting
confidence: 53%
“…Among the most frequently studied GYS1 polymorphisms are the XbaI and Met416Val mutations located in intron 14 and exon 10, respectively (4,5). A number of studies have shown significant associations between these two GYS1 gene markers and type 2 diabetes and hypertension (4,(6)(7)(8), although this is not seen in all reports (5,(9)(10)(11)(12). To our knowledge, whether carriers or noncarriers of a specific GYS1 polymorphism have different GS protein content in their skeletal muscle has only been verified by Groop et al (4).…”
mentioning
confidence: 99%
“…The power of the study strongly depends on the underlying true genetic effect, i.e., the s. By using a not-too-optimistic estimate 2.5 for s, the power to detect linkages with a scores of 3.6 and 3 can be estimated as 60 and 79%, respectively. Within the linkage interval on chromosome 19q13.33-q13.43, the muscle glycogen synthase gene (GYS1) resides, and a polymorphism of this gene has been shown to be associated with the metabolic syndrome and specifically type 2 diabetes in Finnish, French, Japanese, and Pima Indian populations (33). It had been considered a good postulation for inherited skeletal muscle insulin resistance because of the observation of reduced activity in normoglycemic first-degree relatives.…”
Section: Discussionmentioning
confidence: 99%
“…HOMA-IR was calculated as fasting plasma glucose ϫ fasting serum insulin ÷ by 22.5 (20). Phenotypic differences between genotype-discordant sibling pairs were compared using a simulationbased permutation test for paired replicates (21). The permutation test does not make any assumptions about the normality, homogeneity of the variance, or the precise form of the underlying distribution.…”
Section: Methodsmentioning
confidence: 99%